Erosion Corrosion Evaluation of CrN/AlN Multilayer Coatings, by Varying the Velocity and Impact Angle of the Particle - Aperador Chaparro, William Arnulfo; Caballero-Gómez, J.; Delgado Tobón, Emilio (ESG, 2013)
In order to provide solutions to erosion corrosion in industrial devices, thin films of CrN/AlN were deposited on AISI D3 steel substrates using a magnetron sputtering system multitarget with rf (13.56 MHz), from Al and Cr targets of high purity (99.99%) in an atmosphere composed by Ar/N2. The erosion tests and corrosion erosion were made by equipment which lets the change of the impact angle and the jet velocity of the silica particle; moreover the equipment is engaged with a potentiostat. The polarization curves were done in the resting potential. Subsequently of the realization of the polarization curves experiments, the samples were analyzed by scanning electron microscopy. The coating performance is compared with the AISI D3 steel without coating. The degradation mechanisms for PVD coating and uncoated steels have been presented with the help of diagrams wear mechanism.

Con el fin de dar soluciones a la corrosión por erosión en dispositivos industriales, se depositaron películas delgadas de CrN/AlN sobre sustratos de acero AISI D3 mediante un sistema de magnetrón sputtering multiobjetivo con rf (13,56 MHz), a partir de objetivos de Al y Cr de alta pureza (99,99%). en una atmósfera compuesta por Ar/N2. Los ensayos de erosión y erosión por corrosión se realizaron con equipos que permiten cambiar el ángulo de impacto y la velocidad del chorro de la partícula de sílice; además el equipo está acoplado con un potenciostato. Las curvas de polarización se realizaron en el potencial de reposo. Posteriormente a la realización de los experimentos de curvas de polarización, las muestras fueron analizadas mediante microscopía electrónica de barrido. El rendimiento del recubrimiento se compara con el acero AISI D3 sin recubrimiento. Los mecanismos de degradación para aceros con recubrimiento PVD y sin recubrimiento se han presentado con la ayuda de diagramas de mecanismos de desgaste.
Keywords: Erosión; Corrosión; Recubrimientos multicapa; Double layer coatings; multilayered coatings; erosion corrosion; wear; nitrides